The Implication of Digital Technologies and Interventions for Mental Health Care - Thanetnit, Chommakorn (Asian Medical Journal and Alternative Medicine, 2022)
The prevalence of mental health problems during the COVID-19 pandemic was higher than before. Physical distancing policies caused more difficulties in receiving traditional face-to-face mental health care, resulting in wider mental health treatment gaps. Regarding these barriers and the limitation of human resources, digital transformation in psychiatry has been widespread. This article summarized the recent supporting evidence of digital technologies and interventions in psychiatry, including telepsychiatry, computer-based and internet-based cognitive behavioral therapy, smartphone application-based intervention and virtual reality-based therapy, with the most studies for depressive disorders and anxiety disorders. The author also reviewed the usage of mental health chatbots, artificial intelligence, and machine learning. In conclusion, these innovations might be new possibilities in addition to standard psychiatric evaluation and treatment in the upcoming future. However, privacy and security issues remain concerned, which require further studies.